Updates on Laboratory Evaluation of Feline Cardiac Diseases - Alessandra Gavazza; Andrea Marchegiani; Lorenza Guerriero; Vanessa Turinelli; Andrea Spaterna; Sara Mangiaterra; Livio Galosi; Giacomo Rossi; Matteo Cerquetella (Veterinary Sciences, 2021)
Laboratory tests can be altered in cardiovascular diseases and the investigation of specific tests or biomarkers may provide additional information about myocardial damage. Traditional laboratory tests, such as cell blood count, serum biochemistry, and coagulation, can be useful in investigating patients, but are not specific. However, markers like Troponin and Natriuretic Peptides may possibly furnish further data on myocardium damage and can be used in both studying and monitoring cats with cardiac disease. Moreover, the evaluation of the thyroid profile is very important as hyperthyroid cats concomitant cardiovascular diseases are very common and they can also be a direct consequence of endocrinopathy. The purpose of this manuscript is to provide the widest possible overview of what is present in the literature about the feline clinical pathology of heart diseases through a rational division of the main alterations of traditional tests and biomarkers.